Upconverting nanoparticle micro-lightbulbs designed for deep tissue optical stimulation and imaging - Chamanzar, Maysamreza (Biomed Opt Express, 2018)
Optical methods for imaging and stimulation of biological events based on the use of visible light are limited to the superficial layers of tissue due to the significant absorption and scattering of light. Here, we demonstrate the design and implementation of passive micro-structured lightbulbs (MLBs) containing bright-emitting lanthanide-doped upconverting nanoparticles (UCNPs) for light delivery deep into the tissue. The MLBs are realized as cylindrical pillars made of Parylene C polymer that can be implanted deep into the tissue. The encapsulated UCNPs absorb near-infrared (NIR) light at λ = 980 nm, which undergoes much less absorption than the blue light in the brain tissue, and then locally emit blue light ((1)G(4)→(3)H(6) and (1)D(2)→(3)F(4) transitions) that can be used for optogenetic excitation of neurons in the brain. The (3)H(4)→(3)H(6) transition will result in the emission of higher energy NIR photons at λ = 800 nm that can be used for imaging and tracking MLBs through thick tissue.